PENGARUH KOMUNIKASI PRODUKTIF ORANGTUA TERHADAP PERKEMBANGAN EMOSI ANAK - Dian Ismi Islami (Jurnal Pustaka Komunikasi, 2018)
Productive communication is communication carried out from a positive way of thinking so as to produce positive words in delivering messages to the communicant so that they get positive results as well.This study aims to measure the development of Productive Communication on child development. In this study using a quantitative comparison method, this study wants to measure the influence of the large variable X (productive communication) on variable Y (development of child logistics). In the results of the study there is a variable X (VX), namely the importance of productive communication for children, in general, many respondents agree to develop productive communication with children, while in variable Y (VY) that is about developing development development of children who agree to always develop emotional development child in a positive direction. Relating to positive variable X (productive communication) to variable Y (child emotional development). Productive communication can improve children's development by 32.5%